A Channel Drainage Slope Modified as Discharge Supply Chain in the Coastal Area - Wesli Wesli; Said Jalalul Akbar (International Journal of Supply Chain Management, 2020)
Slope in the drainage channel system is a primary factor that determines the quantity of water to be gravity discharged. By having bigger slope, the flow velocity becomes larger and the capacity of water discharged becomes more so that there will be no surface runoff. Lhokseumawe is a city located in the coastal area with its height is only 0.95 m above sea level. It is difficult to build the appropriate slope of the channel. For this reason, innovation is needed by modifying the slope of the channel in stages and tiered at each distance of 50 m, by which for channels along the 1,350 m will have 27 stages. The discharge capacity required to flow the rainfall is based on a 2-year return period of 5.10 m3/ sec. Slopes under normal conditions are 0.0013 to get a flow velocity of 1.27 m/sec. Using a section area of 1.32 m2 channel it can get discharge capacity of 1.67 m3/ sec. Furthermore, the slope of the channel was modified to 0.005 at each distance of 50 m and this obtained a flow velocity of 2.46 m/sec so that it was able to drain a discharge capacity of 3.24 m3/ sec. By modifying this channel slope can increase the discharge by 1.57 m3/sec or 93.7% compared to the slope without modified. It has not been able to multiply the overall discharge but at least can reduce the discharge 93.7%.